Using Emotions to Understand Socially Active Issues in History Lessons - Grez Cook, Francesca (2022)
This article presents an action-research method referring to the implementation of teaching-learning strategies for the development of socio-emotional competencies in high school students in a Chilean school. The idea of this intervention was to strengthen learning about socially living issues in the subject of History, Geography and Social Sciences. The objective of this research is to design a didactic proposal to incorporate self-awareness, self-management and social awareness within History classes. The main results show a high degree of satisfaction in relation to the implementation of new teaching strategies that help understand historical character. Also, students valued the possibility of transferring the socio-emotional exercises done in classes to their own lives, as well as the increase in the motivation during lessons. Additionally, the critical points that have been detected as well as the projections of this experience are analyzed.